ChemInform Abstract: Selenenylations of Alkenes with Styrene Nucleophiles. Issue 20 (25th April 2013) - Gabriele, Elena; Singh, Fateh V.; Freudendahl, Diana M.; Wirth, Thomas
Abstract Iodine‐ and bromine‐mediated treatment of diaryl diselenides with styrene and electron‐rich analogues results in formation of new 2:1 adducts like (III), (VII), and (X).